Outfox - Brown, Sandra, 1948- (Grand Central Publishing, 2019)
FBI agent Drex Easton is driven to outmaneuver the conman known as Weston Graham. When eight women turn up missing, Easton is convinced Graham is responsible and that he murdered them.